Já z hvězd svou moudrost nevyčet... Studentský sborník intermediálních analýz - Janáková, Martina (Masaryk University Press, 2021)
Title in English: Not from the stars do I my judgment pluck...: Students' analytical papers on intermediality The volume consists of two parts, one of which comprises analyses of filmic transmediations of Shakespeare's sonnets (The Sonnetproject, New York Shakespeare Exchange 2013), the other analyses of literary ekphrases (by W. Szymborska, U. Fanthorpe, J. Stone etc.). It results from an Intermedial studies seminar held in 2021 within the program Literature and Intercultural Communication at Masaryk University, Brno. The contributions display various approaches that fall under two main intermedial methods, literature-centered (introduced by Werner Wolf), which focuses primarily on a semantic analysis of the original text, and literature-oriented (as suggested by Irina Rajewsky), which respects the transmediation as an autonomous representation and observes its relations to the pretext mainly retrospectively; and even a comparative one, which involves a translinguistic analysis of translations as intercultural and historical transfers.